Emerging Practices of Contemporaby Subjects in Relation to Technology - Cárdenas Obregón, Karen Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This reflection paper is base don the results of the theoretical approach of the projecto Creation, Political Culture and Education. Wich, is located in the analysis and knowledge of the formas as contemporany subjects are constituted, in relation to technology and its manifestations (Virtuality, media and Information and Communication Technologies). The methodological perspective used was the search, characterization and theoretical conceptualization of some contemporany thinkers (Levy, Virilio, Bauman, Han adn Sibilia). The paper is organized in four moments, first, the subject and the Virtuality, second, the power and the transformation of the subject, followed by the image of “I” and capitalist exhibitionism and, finally, the conclusions. The text pretends to make contributions to the theoretical and conceptual field of education and pedagogy, starting from interdisciplinary postures to make contributions to the theoretical and conceptual field of education and pedagogy, that allow understanding of what type of persons teachers face in the learning processes. These contributions lead to reflection on the aims and times changes that define the information society and its implications for education.